"The body I call 'mine' ": A sense of bodily ownership in Descartes. (13th August 2018) - Chamberlain, Colin
Abstract: How does Descartes characterize the peculiar way in which each of us is aware of our bodies? I argue that Descartes recognizes a sense of bodily ownership, such that the body sensorily appears to be one's own in bodily awareness. This sensory appearance of ownership is ubiquitous, for Descartes, in that bodily awareness always confers a sense of ownership. This appearance is confused, in so far as bodily awareness simultaneously represents the subject as identical to, partially composed by, and united to her body, without distinguishing these relations. Finally, the appearance of ownership is grounded in multiple other ways in which the body sensorily appears: namely, in the fact that the body appears to be inescapable, modified by bodily sensations, and an object of special concern.